PROSEDUR PENGAJUAN PERMOHONAN PEMBATALAN AKTA KELAHIRAN DI PENGADILAN NEGERI YOGYAKARTA - , RAISYAH NUR AGHYA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Birth is an event that requires the presence of a legal regulation that is clear and unequivocal, written so that created a legal certainty within the community. Therefore the Government issued several regulations, including the regulations on the administration of the population one of them is about birth.The birth events need proof being authentic, because to prove the identity of someone definite and can legitimately we see from birth certificate issued by the authorized institution issuing the certificate.But nowadays people often do the filing name changes, improvement names and cancellation of birth certificate for certain reasons.This into the background writer in choosing the theme of reflection internship program report, namely The Procedure of Filling Petition For Annulment of Birth Certificatesin The District Court of Yogjakarta The purpose of internship program is was acquiring knowledge and experience as well as develop skills as practitioners so that it is ready to enter into the real world of work, cultivate and develop students ' experience of the ins and outs of world activity practices work, professional attitude awareness as a potential professional who is responsible for his work.The internship program conducted in the District Court of Yogyakarta for 2 (two) months giving many experiences which are useful for the progress of the author.Besides, writer can increase creativity, skill, insight into how the process of litigants in the courts both in criminal, civil, or filing a legal effort in the verdict that has had the force of law (inkracht). To do cancellation of a birth certificate may apply for a birth certificate cancellation through the District Court by bringing evidence to corroborate the request, such as a photocopy of the Applicant Identity Card, Family Card photocopy, photocopy of birth certificate, copy of citation Deed of Marriage and witnesses.The applicant also must pay a cancellation fee of the birth certificate. Upon completion of the procedure the applicant will be called by the bailiff / bailiff substitute for facing trial after being set and the composition of the panel of judges hearing his case.After getting a letter of Determination the Court then Dept. of population and civil registry will cancel a birth certificate which has been issued with the original Quote interesting birth certificate from the owner and give marginal note in the Certificate Register.